Body Composition and Somatotype of Athletes in the Chilean Sport Talent Development Program - Aedo-Munoz, E (Archivos de Medicina del Deporte, 2023)
Introduction: Determining the body composition and somatotype in sport talents provides a useful reference to improve the trajectory toward high-level competition. Objective: The aim of this study is to determine the body composition and somatotype by discipline of children and adolescents of both genders in the sport talent development program at the Regional Training Center. Material and method: Seventy-two subjects participated (29 females, 15.9 ± 2.0 years; 43 males, 15.9 ± 2.3 years) from the disciplines of athletics, cycling, judo, karate, and table tennis. a) Baseline measurements: weight, height, and body mass index (BMI); b) Body masses by fractioning into five components (in %): muscle, fat, bone, residual and skin, using Kerr s method and c) Somatotype, according to the model proposed by Heath and Carter were performed. Results: Females have a higher percentage of fat mass than males. Exactly the opposite occurs with muscle mass, where males present a higher percentage than females, with the exception of table tennis. Regarding residual mass, males present higher values in all the disciplines. The males were classified as endo-mesomorphs, except for those in athletics, who were classified as ecto-mesomorphs, while the females from athletics and table tennis were classified as central, those from cycling and judo as endomorph-mesomorphs, and those from karate as meso-endomorphs. Conclusion: Through a two-dimensional contrast of the somatotype of CER athletes and that of adult athletes at the High Performance Center in Chile, it was determined that both groups are different, indicating that CER athletes do not yet meet the structural requirements necessary for a trajectory to high-level competition, suggesting that training modifications be considered to get closer to the ideal somatotype. © 2023 Archivos de Medicina del Deporte. All rights reserved.